RETRACTED: Analysis of Scalable Resonant DC–DC Converter Using GaN Switches for xEV Charging Stations - Rajanand Patnaik Narasipuram; Subbarao Mopidevi; Anton Dianov; Amit Singh Tandon (World Electric Vehicle Journal)
In this research, an innovative electric vehicle (EV) charger is designed and presented for xEV charging stations. The key feature of our system is a scalable, interleaved inductor–inductor–capacitor (iL2C) DC-DC converter operation. The proposed system employs two parallel L2C converters with 8-GaN switches on the primary side and a shared rectifier circuit on the secondary side. This configuration not only amplifies the resonant tank internal currents and losses generated by the switches but also improves current sharing. A novel closed-loop technique is proposed with a constant-voltage method of operation, along with a hybrid control scheme of variable frequency + phase shift modulation (VFPSM). To examine the controller and converter’s performance, an experimental demonstration is conducted under varying load conditions, including full load, half load, and light load, where the source voltage and load voltage are maintained at constant levels of 400 Vin and 48 V0, respectively. Furthermore, line regulation is conducted and verified to accommodate a broad input voltage range of 300 Vin–500 Vin and 500 Vin–300 Vin while maintaining an output voltage of 48 V0 at 3.3 kW, 1.65 kW, and 0.33 kW with a peak efficiency of 98.2%.